Analysis Of Work Skills And Work Discipline In Improving Employee Performance At Kayumanis Jimbaran Private Estate & Spa - Puspita, Ni Kadek Diana; Nadra, Nyoman Mastiani; Sutarma, I Gusti Putu (Politeknik Sahid, 2022)
Ni Kadek Diana Puspita1*, Nyoman Mastiani Nadra2, I Gusti Putu Sutarma3 1,2,3Politeknik Negeri Bali, Indonesia *Corresponding: dianapuspita491@gmail.com Diajukan 15-09-2022 Direvisi 22-09-2022 Diterima 25-09-2022 Purpose: This research discusses work skills and work discipline in improving the performance of Kayumanis Jimbaran Private Estate & Spa employees. This study aims to determine the influence of work skills and work disciplines both partially and simultaneously on the performance of employees of Kayumanis Jimbaran Private Estate & Spa and to find out the most dominant variables between work skills and work disciplines in affecting employee performance at Kayumanis Jimbaran Private Estate & Spa.Methods: The population of this study is the employees of Kayumanis Jimbaran Private Estate & Spa, which amounts to 83 people. Data collection techniques in this study are through interviews, observations, questionnaires, and literature studies—data analysis using quantitative primary data analysis processed using multiple regression analysis using the SPSS 25.0 program.Results and discussion: The results of this study show that there is a partial and simultaneous influence of variable work skills and work disciplines on employee performance. The coefficient of determination shows a value of 0.754, which means that Work Skills and Disciplines contributed to influencing Employee Performance by 75.4%, and the remaining 24.6% was influenced by other factors not studied.Implication: The effective contribution shows that the variable Work Skills has a more significant influence on Employee Performance than Work Discipline at 45.44%.